Vejrforholdene i Landbrugsaaret 1883—84.o: fra 1ste Oktbr. 1883 til 30te Septbr. 1884. - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1883—84.o: fra 1ste Oktbr. 1883 til 30te Septbr. 1884.